A propósito de um caso de espessamento cutâneo - Serra, S (2010)
The authors present a clinical case of a 79 years old female patient, with a progressive cutaneous thickening of the face, trunk and limbs, lasting for 6 years. She also presented exertional dyspnea and intermittent solid dysphagia. The laboratory study identified IgG KAPA monoclonal protein and antinuclear antibodies with a speckled pattern. The nailfold capillaroscopy was normal. A detailed physical examination together with cutaneous histopathology led to the diagnosis of Scleromyxedema, a rare cutaneous scleroderma like disease. The differential diagnosis of cutaneous sclerosis is discussed.